Gold(III) phthalocyanine chloride: Optical and structural characterization of thin films. (November 2015) - Basova, Tamara V.; Parkhomenko, Roman G.; Krasnov, Pavel O.; Igumenov, Igor K.; Kadem, Burak; Hassan, Aseel K.
Abstract: In the present work, the investigation of gold(III) phthalocyanine chloride (AuClPc) which received very little attention before is progressed further using a range of optical spectroscopic techniques. Thin films of gold(III) phthalocyanine chloride were produced by organic molecular beam deposition deposition and their structure was investigated by UV–visible spectroscopy, polarization dependent Raman spectroscopy and atomic force microscopy. Experimental observations were confirmed by theoretical analysis using quantum chemical calculations; the latter were used for the detailed assignment of different bands in IR spectra of the gold(III) phthalocyanine chloride. The orientation of gold(III) phthalocyanine chloride molecules relative to the substrate surface was studied in detail using techniques based on the polarization dependent Raman spectroscopy. It was shown that gold(III) phthalocyanine chloride films deposited on quartz substrates at 100 °C exhibit a co-facial structure with the average tilt angles of Pc moieties of ∼70°. Graphical abstract: Highlights: Spectral properties of gold(III) phthalocyanine chloride have been investigated. Experimental and theoretical studies of the vibrational spectra have been performed. Structural features and orientation of AuClPc films have been investigated. AuClPc films exhibit a co-facial structure with a tilt angle of Pc moieties of ∼70°.